Competitiveness Strategy Of Smes Copra In Kempas District With Swot And Ahp Method Approach - Lala Maysarah; Vonny Setiaries Johan; Yossie Kharisma Dewi (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2026)
Purpose: The purpose of this research is to analysis strategies to improve the competitiveness of copra Small and medium enterprises (SMEs) in Kempas District. Methodology: This research uses a survey method, research sampling using purposive sampling. The research respondents included Respondents in the SWOT analysis were 7 owners of copra agro-industry, 2 intermediary traders, 1 BRI Bank, the Head of Kempas Sub-district, and the Head of the Agricultural Extension Center (BPP) coordinator and respondents who became experts in the AHP analysis were one exporter (CV Amarta), one intermediary trader and the Head of the Kempas Sub-district Agricultural Extension Center (BPP) coordinator. Results The survey results were followed by Strengths, Weakness, Opportunities, and Threats (SWOT), including internal factor analysis and external factor analysis then analysis with the method Analytical Hierarchy Process (AHP) to select alternative copra SMEs competitiveness strategies. Based on SWOT, the results of internal analysis include 4 strength factors and 6 weakness factors, while external analysis obtained 5 opportunity factors and 4 threat factors. Analysis using the SWOT matrix shows that there are 7 strategies for the competitiveness of copra SMEs in Kempas District. The next stage is to select alternative competitiveness strategies using the AHP method based on selected criteria, namely machine, method, and material. The strategy recommendations obtained based on these criteria are the use of a dryer with a score of 0.230, determining the appropriate raw material specifications with a score of 0.195 and building partner trust with a score of 0.143. Novelty: This study systematically integrates SWOT and AHP approaches to determine the competitiveness strategy of copra UMKM based on technical and operational priorities at the sub-district level. Type of Paper: Identifisuch as a research article.